2011
DOI: 10.1016/j.jecp.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Are children’s faces really more appealing than those of adults? Testing the baby schema hypothesis beyond infancy

Abstract: The present study examined adults’ evaluations of likeability and attractiveness of children’s faces from infancy to early childhood. We tested whether Lorenz’s baby schema hypothesis (1943) is applicable not only to infant faces but also to faces of children at older ages. Adult participants were asked to evaluate children’s faces from early infancy through to 6 years of age in terms of their likeability and attractiveness, and these judgments were compared to those of adult faces. It was revealed that adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
69
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 31 publications
10
69
1
1
Order By: Relevance
“…We found that the actual face age of children significantly and negatively predicted likeability judgments of participants without siblings ( t = −6.37, p < 0.001, R 2 = 0.22). The older the face age, the less likeable the participants judged the faces, confirming previous findings (Luo, et al, 2011). However, no significant face age effect was found for participants with siblings ( t = −1.75, p = 0.082, R 2 = 0.02) who failed to show a face age related decline in likeability judgments (Fig.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…We found that the actual face age of children significantly and negatively predicted likeability judgments of participants without siblings ( t = −6.37, p < 0.001, R 2 = 0.22). The older the face age, the less likeable the participants judged the faces, confirming previous findings (Luo, et al, 2011). However, no significant face age effect was found for participants with siblings ( t = −1.75, p = 0.082, R 2 = 0.02) who failed to show a face age related decline in likeability judgments (Fig.…”
Section: Resultssupporting
confidence: 90%
“…1). All faces had neutral emotional expressions, confirmed by an additional group of 36 adult raters (for details, see Luo, et al, 2011). …”
Section: Methodsmentioning
confidence: 76%
See 2 more Smart Citations
“…The link between baby schema and perceptions of cuteness extends to the age of about 4.5 years (Luo, Lee, & Li, 2011), which may reflect a decreased reliance on parental care with age. The link between cuteness, health, and caretaking motivation may serve an adaptive functionthat is, to optimize allocation of parental resources according to perceived offspring quality or viability as a sick infant simultaneously increases the cost of parental investment and decreases the chances of investment payoff.…”
Section: Infant Cutenessmentioning
confidence: 99%